The Evolution of Family Roles: Towards Greater Gender Equality (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2025)
For the purposes of this article, the objective is to analyze the evolution of family roles in different sociocultural contexts to identify the factors that have influenced the transformation of gender dynamics and their contribution to gender equity in contemporary family relationships. This article was based on a qualitative approach where ten articles from the journals Dialnet and Redalyc were reviewed, considering characteristics for analysis. It concludes that traditional roles have been replaced by a more equitable distribution of family responsibilities, with greater female participation in the labor market and greater awareness of gender equality. New forms of family organization, such as single-parent and collective families, reflect this transformation.
Keywords: Gender equity; well-being; role distribution; family inequality